2019
DOI: 10.1111/jmcb.12686
|View full text |Cite
|
Sign up to set email alerts
|

Monetary News Shocks

Abstract: We pursue an empirical strategy to identify a monetary news shock in the U.S. economy. We use a monetary policy residual, along with other variables in a vector autoregression (VAR), and identify a monetary news shock as the linear combination of reduced‐form innovations that is orthogonal to the current residual and that maximizes the sum of contributions to its forecast error variance over a finite horizon. Real GDP declines in a persistent manner after a positive monetary news shock. This contraction in eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
(76 reference statements)
0
5
0
1
Order By: Relevance
“…Although forward guidance seems to be effective in moving medium-to long-term interest rates at high frequencies, 4 the empirical evidence on its effectiveness in mov-ing key macroeconomic variables is still relatively scarce. Some exceptions are Andrade and Ferroni (2019), Smith and Becker (2015), Bundick andSmith (2018) andBen Zeev et al (2019). Andrade and Ferroni (2019) find that the ECB was successful in stimulating the economy when it was surprising the market with Odyssean signals of future policy accommodation.…”
Section: Introductionmentioning
confidence: 99%
“…Although forward guidance seems to be effective in moving medium-to long-term interest rates at high frequencies, 4 the empirical evidence on its effectiveness in mov-ing key macroeconomic variables is still relatively scarce. Some exceptions are Andrade and Ferroni (2019), Smith and Becker (2015), Bundick andSmith (2018) andBen Zeev et al (2019). Andrade and Ferroni (2019) find that the ECB was successful in stimulating the economy when it was surprising the market with Odyssean signals of future policy accommodation.…”
Section: Introductionmentioning
confidence: 99%
“…The current paper takes the first step to disentangle the unanticipated monetary shock from the endogenous response of monetary policy to the TFP news shock. Recent studies also highlight the importance of other news shocks identified with the maximum forecast error variance decomposition approach in the spirit of Barsky and Sims (2011), such as the risk news shock [Pinter et al (2013)], the fiscal news shock (Ben Zeev and Pappa (2017)), the monetary news shock [Kapinos (2011) andBen Zeev et al (2020)], and the investment-specific news shock [Ben Zeev and Khan (2015) and Ma (2018)]. The approach proposed in this paper provides a way to combine the zero restriction method with the maximum forecast error variance decomposition approach.…”
Section: Discussionmentioning
confidence: 99%
“…They find news shocks play an important role in matching data. Ben Zeev, Gunn, and Khan (2015) and Campbell et al (2012) develop methods to identify anticipated monetary policy shocks in the data. expectations, and they are only effective in periods when the expected policy rate is above zero.…”
Section: Introductionmentioning
confidence: 99%
“…They find news shocks play an important role in matching data. Ben Zeev, Gunn, and Khan () and Campbell et al () develop methods to identify anticipated monetary policy shocks in the data.…”
mentioning
confidence: 99%